Exploring Student Perspectives on Digital Peer Feedback in Process-Based Second Language Writing: Inquiry Study - Endar Rachmawaty Linuwih (Universitas PGRI Madiun, 2026)
This study investigates the role of online peer feedback in second language (L2) writing within an Indonesian university context. The primary aim is to explore how L2 writers (n = 26) perceive the benefits of engaging in a discussion forum on Moodle, used as a Learning Management System (LMS), for online peer evaluation in an academic writing course. Employing a qualitative case study design, data were collected from students’ essays, LMS-mediated peer comments, and self-reflection papers. The data were analysed inductively following Braun and Clarke’s thematic analysis framework to identify emergent themes. Results indicate that participating in an online writing community not only enhanced the students’ ability to perceive and utilize feedback effectively, but also fostered a shared understanding of feedback practices, ultimately establishing a supportive writing community. In addition, the online peer feedback experience was found to significantly boost students’ critical thinking skills—an essential aspect of the writing process. The study concludes that incorporating technology-enhanced interactive social settings in L2 writing instruction can lead to substantial improvements in both feedback engagement and writing proficiency.